Dampak Inovasi Layanan Samsat Keliling Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus Kantor Samsat Sumenep) - Ade Fariska; Isnani Yuli Andini (MAMEN: Jurnal Manajemen, 2023)
The Impact of Mobile Samsat Service Innovation on Motor Vehicle Taxpayer complione (a case of the Sumenep Samsat office). Theisis : Accounting study program, Fakulty of conomics and Businees, Wiraraja University. Supervisor : Isnani Yuli Andini S.,.M.Ak. This study aims to determine the impact of mobile Samsat service innovation on motor vehicle taxpayer compliance. Tax is a fee that can be imposed without reciprocal services or direct compensation. This research is a qualitative research. The data sourced from interviews through a list of texts obtained through informants who were sampled in the study. Data analysis used data reduction analysis, data presentation and counclusion drawing. The results of the data reduction analysis showed that the exintence of mobile Samsat services had a positive impact, both for the Samsat office and the community on motor vehicle taxpayer compliance. Analysis of data presentation shows that there is a mobile samsat on motorized vehicle tax compliance, which has increased every year. The analysis concludes that the existence of mobile Samsat innovation services has a positive impact on the community and the Samsat office. The impact is to make it easier for people to pay taxes, especially taxpayers who live far from the Samsat office. So that with the existence of a circular samsat, taxpayer compliance is increasing.The obstacles faced when the mobile samsat service took place were problems in the internet network section and when rhe samsat office held evenrs. This is what makes mobile samsat service unable to operate properly and on time.